THE EFFECT OF THE APPLICATION OF THE FULL COSTING METHOD ON THE ACCURACY OF SELLING PRICE DETERMINATION IN MSMES - Elton Ramos (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This study aims to analyze the effect of the full cost method on the accuracy of selling price determination among MSMEs in the Berastagi Fruit Market, Karo Regency. This study is motivated by pricing practices that do not systematically account for all production cost components, potentially leading to pricing inaccuracies. The study employed a quantitative approach with a survey method. Primary data was obtained through a structured questionnaire distributed to 20 MSMEs selected using purposive sampling. The criteria were that they had been operating for at least two years, had production or processing activities, and set their own selling prices. The data were analyzed using descriptive analysis and simple linear regression. The results indicate that the implementation of the full cost method is in the good category and has a positive effect on the accuracy of selling price determination. MSMEs that calculate production costs more fully tend to set prices that are more in line with their cost structure, thus supporting profit stability and business sustainability. Limitations of this study lie in the limited sample size and location coverage. Therefore, further research is recommended to expand the sample and variables to make the results more comprehensive and have stronger generalizability